Relationship between Disease Activity and Calcium Levels with Bone Mineral Density in Rheumatoid Arthritis Patients - Megawanto, Nur Handy; Suryana, Bagus Putu Putra; Rosandi, Rulli (Clinical and Research Journal in Internal Medicine, 2021)
Background: Arthritis rheumatoid (AR) is a chronic inflammatory disease that mainly affects the joints. Decreased bone mass and osteoporosis are its complications. Several factors such as dietary calcium, disease activity, physical activity, vitamin D levels, steroids can affect bone mineral density values. Aim: The purpose of this study was to determine the relationship between disease activity, calcium levels and bone mineral densitometry in patients with arthritis rheumatoid. Methods: 23 AR patients based on the 2010 ACR criteria including the inclusion criteria with a cross sectional study approach that had bone mineral densitometry (BMD) data for the last 1 year. Blood samples were also taken to check the total calcium level, the characteristics of the baseline data were collected, and the disease activity was examined using the DAS 28 LED. The relationship between these factors and the bone mass density was analyzed using the Spearman test. The analysis result was considered significant if p <0.05. Results: The results showed that the basic characteristics of the subjects were 45,87 years old, body mass index 24,51 kg / m2, duration of illness 3,96 years, steroid dose 3,48 mg, disease activity 4.35 (moderate disease activity), anti CCP 333,87 U / ml, rheumatoid factor (RF) 10,18 IU / ml, methotrexate 12,17 mg, leflunomide 20 mg. There was no significant relationship between serum calcium levels and disease activity with BMD. However, there was a significant relationship between age and BMI with BMD in the femur neck (p = 0,043), lumbar 3 (p = 0,017) and lumbar 4 (p = 0,048). Conclusion: There is no relationship between disease activity and calcium levels with bone mass density values in AR patients except for age and BMI.